Relative Sowing Time and Spatial Arrangement in Upland Rice/Legume Intercropping Systems - Meirelles, Flávia Constantino [UNESP]; Cavalcante, Adailza Guilherme [UNESP]; Gonzaga, Alex Rangel [UNESP]; Coelho, Anderson Prates [UNESP]; van der Werf, Wopke; Bastiaans, Lammert; Arf, Orivaldo [UNESP]; Lemos, Leandro Borges [UNESP] (Springer Nature, 2024)
Legumes can be integrated into cereal crop systems as a service crop to fix nitrogen, support cereal grain quality, and provide fodder for animals. However, competitive effects on cereal crop yields need to be avoided as much as possible. Here, we study the effect of seven legume species on yield, yield components and grain quality of rice, in dependence of the relative sowing time of the legume and the spatial configuration of the intercrop. In the first year, legume species were sown simultaneously with rice as well as at 25 days after rice emergence (DARE). Based on the first year, legume species were only sown at 25 DARE in the second year, but in two spatial configurations: alternate and double row design. Rice grain yield and total dry mass were negatively associated, showing the difficulty in obtaining an increased biomass production without giving in on rice grain yield. There are legumes species (Crotalaria spectabilis, jack bean and dwarf pigeon pea) that compete more with upland rice than others and legumes sowing at 25 DARE and in double rows reduces this competitive effect. Overall, upland rice intercropped with C. breviflora presented a higher total dry mass production than sole rice, without affecting grain yield. The crude protein content of rice grains was higher in intercrops in which grain yield was reduced by legumes due to the dilution effect. The adjustments in sowing time and spatial arrangement increased the range of legume species that can be used to promote ecological benefits without negatively affecting rice yield and quality, enabling diversification of species and biomass in the same area, associating food production with the benefits of the legume ecosystem services.
Keywords: Cover crops; Double rows design; Ecosystem services; no-tillage; Oryza sativaL; Polyculture